Penyelesaian Kumulasi Perkara Isbat Nikah dan Cerai Talak dalam Putusan Nomor 0307/Pdt.G/2018/PA.Sby - Alfiyah Faizatul Arif (MASADIR: Jurnal Hukum Islam, 2024)
In the practice of proceedings in the Religious Courts, judges generally immediately apply Article 7 Paragraphs (2) and (3) of the Compilation of Islamic Law (KHI) without testing the strength of its enforceability before the law. Thus, even though these provisions are difficult to understand, the majority of Religious Court judges, with their interpretation, understand the provisions in Paragraph (3) letter a, as if it is mandatory to accept the application for itsbat marriage if it is submitted in combination with the application for talak divorce, even though the marriage was carried out after its entry into force. Law no. 1 of 1974. The consideration of the marriage isbat law itself is still a matter of polemic. Bearing in mind that the position of KHI which is the basic reference for legal considerations by judges is not included in the statutory hierarchy. This happened in the divorce divorce case Decision Number 0307/Pdt.G/2018/PA.Sbg. Several issues can be raised that become a polemic regarding the marriage isbat law, namely how the essence of the marriage isbat law is related to the essence of the marriage isbat law in the marriage legal system in Indonesia. Then what is the legal position of marriage isbat in the Religious Courts which was implemented after Law Number 1 of 1974. The provisions for marriage isbat in Indonesia only came into existence after the birth of Law Number 1 of 1974 concerning Marriage. In addition, the law has given legitimacy to judges to further explore the values ??and sense of justice in society.